Prognostic value of HIFs expression in head and neck cancer: a systematic review. - Liang Gong; Wei Zhang; Jianding Zhou; Jie Lu; Hua Xiong; Xueli Shi; Jianqiang Chen (PLoS ONE)
Background Tumor hypoxia plays a fundamental role in resistance to therapy and disease progression. A number of studies have assessed the prognostic role of HIFs expression in head and neck cancer (HNC), but no consistent outcomes are reported. Methodology A systematical search was performed to search relevant literatures in PubMed, Web of Science and ISI Web of Knowledge databases. The patients' clinical characteristics and survival outcome were extracted. The correlation between HIFs expression and prognosis was analyzed. Principal findings A total of 28 studies assessed the association between HIFs and HNC survival, the result showed that overexpressed HIFs was significantly associated with increase of mortality risk (HR = 2.12; 95% CI: 1.52-2.94; I(2) 74%). Subgroup analysis on different HIF isoforms with OS indicated that both HIF-1α and HIF-2α were associated with worse prognosis. The pooled HRs were 1.72(95% CI 1.34-2.20; I(2) 70.7%) and 1.79(95% CI: 1.42-2.27, I(2) 0%). Further subgroup analysis was performed by different geographical locations, disease subtype, stage, types of variate analysis and cut-off value. The results revealed that overexpressed HIF-1α was significantly associated with poor prognosis in Asian patients (HR = 2.34; 95% CI: 1.76-3.1; I(2) 48.9%), but not in European patients (HR = 1.13; 95% CI: 0.77-1.66; I(2) 78.3%). Furthermore, HIF-1α overexpression was significantly associated with worse OS in oral carcinoma (HR = 2.1; 95% CI: 1.11-3.97; I(2) 81.7%), nasopharyngeal carcinoma (HR = 2.07; 95% CI:1.23-3.49; I(2) 22.5%) and oropharynx carcinoma (HR = 1.76; 95% CI:1.05-2.97; I(2) 61%), but not in laryngeal carcinoma (HR = 1.38; 95% CI: 0.87-2.19; I(2) 62.5%). We also found that the prognostic value of HIF-1α overexpression existed only when using staining and percentage as positive definition (HR = 1.82; 95% CI 1.42-2.33; I(2) 9.9%). Conclusions This study showed that overexpressed HIFs were significantly associated with increase of mortality risk. Subgroup analysis revealed that overexpressed HIF-1α was significantly associated with worse prognosis of HNC in Asian countries. Additionally, HIF-1α had different prognostic value in different HNC disease subtypes.